Multiple Cycloaddition Reactions of Ketones with a β‐Diketiminate Al Compound. Issue 52 (23rd November 2015) - Sarish, Sankaranarayana Pillai; Samuel, Prinson P.; Roesky, Herbert W.; Schulzke, Carola; Nijesh, Karikkeeriyil; De, Susmita; Parameswaran, Pattiyil
Abstract: A β‐diketiminate Al compound (1 ) with an exocyclic double bond reacts with two equivalents each of benzophenone and 2‐benzoylpyridine in a [4+2] cycloaddition to generate bicyclic and tricyclic compounds 2 and 3, respectively. Compound 2 consists of six‐ and eight‐membered aluminium rings, whereas 3 has two five‐ and one eight‐membered ring. Compounds 2 and 3 were characterized by a number of analytical tools including single‐crystal X‐ray diffraction. The quantum mechanical calculations suggest that the dissociation of the solvent molecule from 1 would lead to an active species 1A having two 1, 4‐dipolar 4π electron moieties, in which the electrophilic site is the Al atom and the nucleophilic positions are polarized exocyclic and endocyclic CC π bonds. The detailed mechanistic study shows that the dipolarophiles, benzophenone, and 2‐benzoylpyridine undergo double cycloaddition with two 1, 4‐dipolar 4π electron moieties of 1A . Herein, the addition of one molecule of the dipolarophile promotes the addition of the second one. Abstract : Two molecules each of benzophenone and 2‐benzoylpyridine undergo successive [4+2] cycloaddition with [L 1 AlMe]⋅ THF (L 1 =CH[C(CH2 )](CMe)(2, 6‐ i Pr2 C6 H3 N)2 ) to form bi‐ and triheterocyclic aluminium compounds, respectively (see scheme).